1977
DOI: 10.1093/infdis/136.4.510
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Metabolic and Chemiluminescent Responses of Granulocytes from Three Female Siblings with Chronic Granulomatous Disease

Abstract: Polymorphonuclear leukocytes (PMNL) from children with atypical chronic granulomatous disease (CGD), their mother and siblings, and normal controls were studied in regard to glycolytic and hexose monophosphate shunt activities in the resting, methylene blue-stimulated, and phagocytizing states. PMNL from the patients with CGD had normal glycolytic and hexose monophophate shunt activities in the resting state and after stimulation with methylene blue. However, stimulation of the hexose monophosphate shunt after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

1980
1980
1994
1994

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 33 publications
2
8
0
1
Order By: Relevance
“…Another rarely applied parameter to define phagocyte activity is the initial slope of the stimulation curve (ALLEN et al, 1977;STEVENS et al, 1978). We took the maximal increase between two determination points of the ascending loop of the stimulation curve as a percentage of the maximal CL.…”
Section: Discussionmentioning
confidence: 99%
“…Another rarely applied parameter to define phagocyte activity is the initial slope of the stimulation curve (ALLEN et al, 1977;STEVENS et al, 1978). We took the maximal increase between two determination points of the ascending loop of the stimulation curve as a percentage of the maximal CL.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, we have demonstrated that increased levels of indomethacin-sensitive suppressor function are directly correlated with increased conversion of arachidonic acid to prostaglandins of the E series on the part of peripheral blood glass-adherent cells [8]. There is a substantial body of evidence which suggests that CL provides a reliable, quantifiable assay of oxidative metabolism in reticuloendothelial cells [2,4,5,6]. Macrophage activation has been assessed using CL [30], and human monocytes also respond with light emission to a variety of stimuli [20,25].…”
Section: Discussionmentioning
confidence: 99%
“…There is a substandial body of evidence which suggests that CL provides a reliable, quantifiable assay of oxidative metabolism in reticuloendothelial cells [1,3,4,6], and with appropriate modifications, can also be used to measure particle uptake [12] or serum opsonic activity [1,2]. Macrophage activation has been assessed by means of CL [25], and since human monocytes also respond with light emission to a variety of stimuli [16,20], it is reasonable to suggest that the enhanced CL from the PBMC of patients with advanced cancer reflects an in vivo stimulation, although CL alone cannot provide any direct information on the nature of the stimulus.…”
Section: Discussionmentioning
confidence: 99%